Comparative Analysis In Body Length Of Low Birth Weight (Lbw) According To The Usage Of Exclusive Mother’s Breastmilk And To The Usage Formula Milk To 0-2 Weeks At Saint Elizabeth Hospital Medan In 2011-2014 - Trivo Sana Rajagukguk; Evawany Y Aritonang; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Low Birth Weight is when an infant born with less than 2500 grams without looking at pregnancy. Breastfeeding is the best way to feed the infants. However, for some reasons mothers opt to add or replace breastmilk. An infant is classified as stunting if they has length of birth <46,1cm for male and < 45,4cm for female. Stunting is short stature caused by chronic malnutrition. This research aims to understand the difference in body length of LBW infants fed through the use of breastmilk or formula milk in the first two weeks of treatment at Saint Elizabeth Hospital Medan in 2011-2014. This research is using cross-sectional design. The participants consist of 56 infants of LBW with the age of two weeks under the treatment of Saint Elizabeth Hospital Medan in 2011-2014. This research using secondary data of medical record documentation in the Prenatal Hospital. Data analysis was performed using Independent Samples T-Test. The results shows that there is no significant difference between the increase in body length of breast-fed babies who were given with the increase in body length babies fed milk formula with p value (0,46) > α (0,05). Researchers suggest that in order to further improve the service to the handling of the problem of low birth weight, especially in the provision of nutrition for infants of low birth weight hospital institutions, nurses who worked in chambers of perinatology should be support and motivate mothers to breastfeed their infants and consider the condition of an infant during the maintenance. Keywords : low birth weight, breastfeeding, formula milk, weight, body length.